2017
DOI: 10.1136/bjsports-2016-096723
|View full text |Cite
|
Sign up to set email alerts
|

Sitting behaviour is not associated with incident diabetes over 13 years: the Whitehall II cohort study

Abstract: WHAT ARE THE NEW FINDINGS The epidemiological literature on sitting and incident diabetes is very scant and rarely acknowledges the confounding role of adiposity  Occupational, non-TV leisure time at home, and total non-TV sitting were not associated with incident diabetes risk over 13 years of follow-up  TV time and total sitting were associated with diabetes but once baseline body mass index was taken into account these associations were attenuated HOW MIGHT IT IMPACT ON CLINICAL PRACTICE IN THE NEAR FUTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Eight articles reporting more than one health outcome were treated as independent studies . Among these studies, 21 studies (six cohort and 15 cross‐sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 23 studies (13 cohort and 10 cross‐sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, and 14 studies (one cohort and 13 cross‐sectional studies) examined the association between total sedentary behaviour and hypertension . Ten studies were conducted in North America, two in South America, nine in Australia, 18 in Europe, seven in Asia, and two in other regions .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight articles reporting more than one health outcome were treated as independent studies . Among these studies, 21 studies (six cohort and 15 cross‐sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 23 studies (13 cohort and 10 cross‐sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, and 14 studies (one cohort and 13 cross‐sectional studies) examined the association between total sedentary behaviour and hypertension . Ten studies were conducted in North America, two in South America, nine in Australia, 18 in Europe, seven in Asia, and two in other regions .…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles reporting more than one health outcome were treated as independent studies. [28][29][30][31][32][33][34][35] Among these studies, 21 studies (six cohort and 15 cross-sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 32-52 23 studies (13 cohort and 10 cross-sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, [28][29][30][31][32][33]35,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] and 14 studies (one cohort and 13 cross-sectional studies) examined the association between total sedentary behaviour and hypertension. 27 Research and Quality scale for cross-sectional studies, which indicated that the included studies were of high quality (Table S3A,B in Appendix S1).…”
Section: Characteristics and Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of cases in the highest reported category of sedentary behaviour was divided by the proportion of people at baseline in the highest category to produce an adjustment factor. For example, Stamatakis et al 12 reported that 34.1% of all study participants and 38.3% of diabetes cases were sedentary at baseline. The adjustment factor was 1.12 (38.3/34.1).…”
Section: Methodsmentioning
confidence: 99%
“…Representation of the misleading dichotomous impression conveyed by a single 95% confidence interval . The 95% confidence interval for the hazard ratio (HR) obtained by Stamatakis et al comparing incident type 2 diabetes among the group with the highest amount of sitting time versus the lowest. The black dot denotes the point estimate (HR = 1.19), and the vertical dashed line denotes the null value (HR = 1)…”
Section: Introductionmentioning
confidence: 99%